Ω‐3 Supplementation increases amyloid‐β phagocytosis and resolvin D1 in patients with minor cognitive impairment. Issue 7 (24th March 2015) - Fiala, Milan; Halder, Ramesh C.; Sagong, Bien; Ross, Olivia; Sayre, James; Porter, Verna; Bredesen, Dale E.
ABSTRACT: We investigated the effects of 4–17 month supplementation with ω‐3 fatty acids and antioxidants (Smartfish drink; Smartfish AS, Oslo, Norway) in 12 patients with minor cognitive impairment (MCI) [mini‐mental state examination (MMSE) ≥19], 2 patients with pre‐MCI (normal MMSE), and 7 patients with Alzheimer disease (AD) (MMSE <19). We measured the phagocytosis of amyloid‐β 1‐42 (Aβ) by flow cytometry and microscopy, the transcription of inflammatory genes by RT‐PCR, the production of resolvin D1 (RvD1) by enzyme immunoassay, and the cognitive status by MMSE. In patients with MCI and pre‐MCI, phagocytosis of Aβ by monocytes increased from 530 to 1306 mean fluorescence intensity units ( P = 0.016). The increase in patients with AD was not significant (N.S.). The lipidic mediator RvD1, which stimulates Aβ phagocytosis in vitro, increased in macrophages in 80% of patients with MCI and pre‐MCI (mean increase 9.95 pg/ml) (N.S.). Transcription of inflammatory genes' mRNAs was increased in a subgroup of patients with low transcription at baseline, whereas it was not significantly changed in patients with high transcription at baseline. The mean MMSE score of patients with MCI and pre‐MCI was 25.9 at baseline and 25.7 after 4‐17 months (N.S.). Our study is the first to show significant immune and biochemical effects of ω‐3 fatty acids with antioxidants in patients with MCI. Cognitive benefits of ω‐3 supplementation in patients with MCI should be tested in a clinical trial.—Fiala, M., Halder, R. C., Sagong, B., Ross, O., Sayre, J., Porter, V., Bredesen, D. E. ω‐3 Supplementation increases amyloid‐β phagocytosis and resolvin D1 in patients with minor cognitive impairment. FASEB J . 29, 2681‐2689 (2015). www.fasebj.org